PROBLEMATIKA PERNIKAHAN MUALLAF DI LOKSADO: SEBUAH ANALISIS HUKUM DAN SOSIAL - Aseri, Muhsin (CV. Lafadz Jaya, 2024)
This article aims to explore the problems of Muslim convert marriages in Loksado, especially regarding the process and registration of marriages. This research is field research with a qualitative descriptive approach. The research subjects included Muslim convert couples who had married in Loksado. Data was obtained through structured interviews and document study. The research results show that there are significant problems in registering marriages of converts to Islam, especially for those who were previously married according to the Kaharingan belief. The main obstacles include the absence of a divorce certificate, death certificate, and legalization of marriages entered into before converting to Islam. Factors that influence this problem include low levels of education, understanding of administration, and economic factors. In addition, differences in views were found between Islamic law and Indonesian positive law regarding remarriage after converting to Islam. This article provides an in-depth view of the need for administrative reform and legal policy to protect the rights of converts to marriage.